Buckling Behavior of a Functionally Graded Sandwich Plate - Gupta, Anil Kumar; Kumar, Ajay (Engineering, Technology & Applied Science Research, 2023)
This research focuses on the buckling behavior of a porous Functionally Graded (FG) sandwich plate using the sinusoidal shear deformation theory and hyperbolic tangent and secant thickness stretching functions with novel displacement fields. The proposed model assumes a different thickness layer system with FGM on the top and bottom and a ceramic core. Hamilton’s energy principle is applied to the FGM sandwich plates to understand their buckling behavior. The mesh convergence on Finite Element (FE) model is carried out, and the accuracy of the results is tested using the existing research. The present model results match reasonably well with the previously published literature. The impact of the transverse shear deformation, plate aspect ratio, size-to-thickness ratio, and volume fraction is investigated for different thickness layer systems.